A Study on Linear Inequality Representation of Social Welfare Functions - Keisuke Sato; Yoshitsugu Yamamoto (Tinbergen Institute, 2006)
This paper presents a study on the recently proposed linear inequality representation of Arrovian Social Welfare Functions (ASWFs). We first give an alternative proof of the ASWF integer linear inequality representation theorem, and then show several sufficient conditions on preference domains for the linear inequalities of the representation to form integral polytopes. We also show that a given probabilistic ASWF induces a real vector satisfying the inequalities.
Keywords: D71; 330; Social welfare function; Linear inequality representation; Extreme points; Probabilistic social welfare function; Integral polytope